Female labour countries supply and mortgate-related borrowing constraints - Li, Chen (Université d'Ottawa | University of Ottawa, 2004)
This paper uses data from the 1996 Canadian Family Expenditures Survey to examine the relationship between female labour supply decisions and mortgage-related borrowing constraints in a life-cycle model. The analysis is restricted to married couples in wh